2005
DOI: 10.1016/j.jinf.2004.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Serum copper and zinc concentrations in patients with chronic hepatitis B

Abstract: The aim of this study was to measure the alterations in serum trace elements, including zinc and copper in patients with chronic hepatitis and to compare with the results of healthy individuals. The serum zinc and copper concentrations were measured by using atomic absorption spectrophotometer in sera of patients with chronic hepatitis and statistically compared with those of healthy individuals. One hundred and five subjects, 71 patients with chronic hepatitis B (46 asymptomatic carriers, 25 chronic active he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
(8 reference statements)
0
9
0
2
Order By: Relevance
“…Several small studies have evaluated serum zinc levels in patients with chronic viral hepatitis. [69][70][71][72][73][74] The results have been mixed. Three found no significant differences when compared with controls; however, others have demonstrated a signifi-cant decrease in serum zinc levels when compared with controls.…”
Section: Zinc In Viral Hepatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Several small studies have evaluated serum zinc levels in patients with chronic viral hepatitis. [69][70][71][72][73][74] The results have been mixed. Three found no significant differences when compared with controls; however, others have demonstrated a signifi-cant decrease in serum zinc levels when compared with controls.…”
Section: Zinc In Viral Hepatitismentioning
confidence: 99%
“…Three found no significant differences when compared with controls; however, others have demonstrated a signifi-cant decrease in serum zinc levels when compared with controls. [69][70][71][72][73][74] In one of these studies, a significant difference was found only in those patients with cirrhosis. 72 Another of these studies only looked at patients with chronic hepatitis C and demonstrated that, in addition to lower serum zinc levels at baseline, these reductions were exacerbated further following injection of INF-α.…”
Section: Zinc In Viral Hepatitismentioning
confidence: 99%
“…Many studies have been conducted to examine the relationship between serum Cu and serum Zn levels and various diseases, especially infectious diseases. 1,2,4,5,7,8,10,11,13,14,18 This is the first study that compares the serum Cu/Zn ratios in patients with brucellosis and individuals in two different control groups. In general, there are two types of abnormalities in the levels of trace elements.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,12 Different studies have investigated the diagnostic value or metabolic alterations of Cu and Zn, particularly in infectious diseases. 1,2,4,5,11,13,14 Brucellosis is a zoonotic infectious disease that is endemic in the Southeastern region of Turkey. The morbidity of disease is rather high, while its mortality is very low.…”
mentioning
confidence: 99%
“…However, the pattern of trace element changes is not the same in different infections. For example, clinical studies in patients with brucellosis show changes in Cu and Zn (Cesur et al, 2005c), whereas hepatitis B (Cesur et al, 2005a) and C (Cesur et al, 2005b) infections does not affect these elements. The most consistent responses include a decrease in plasma levels of Fe and Zn and an increase in Cu (Beisel, 1998;Ilback et al, 2003b;Pekarek and Engelhardt, 1981).…”
Section: Changed Metabolism In Infectionmentioning
confidence: 99%